PERAN DIGITAL MARKETING BAGI WIRAUSAHA PEMULA DI DESA SAMBONG DUKUH KABUPATEN JOMBANG - Aliffia Agustina Nugraha; Eka Novita Sari; Navissya Dzuchroidah; Afiyah Nur K (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2021)
This community service is aimed at the youth of Sambong Dukuh Village, Jombang District, Jombang Regency, East Java Province as individuals or groups who are expected to be able to increase the number of new entrepreneurs so that they can create and increase the income of villagers. This service activity is carried out by providing education on the importance of entrepreneurship since adolescence and the ease of promotion in the digital era by utilizing social media as a business opportunity to get more turnover and not require a lot of spending. In addition, this service activity not only provides education on the importance of entrepreneurship since adolescence, but this service activity invites teenagers to remain productive during the current pandemic. Keywords: Digitalization, Marketing, Entrepreneurship